Roles of AaVeA on Mycotoxin Production via Light in Alternaria alternata - Wang, Liuqing; Wang, Meng; Jiao, Jian; Liu, Hongmei (Frontiers in Microbiology, 2022)
Alternaria alternata is a principal plant pathogen responsible for the biosynthesis of mycotoxins, including tenuazonic acid (TeA), alternariol (AOH), and alternariol monomethyl ether (AME). The velvet gene VeA is involved in fungal growth, development, and secondary metabolism, including mycotoxin biosynthesis via light regulation. In this study, the detailed regulatory roles of AaVeA in A. alternata with various light sources were investigated from the comparative analyses between the wild type and the gene knockout strains. In fungal growth and conidiation, mycelial extension was independent of light regulation in A. alternata. Red light favored conidiation, but blue light repressed it. The absence of AaVeA caused the marked reduction of hyphae extension and conidiophore formation even though red light could not induce more spores in ΔAaVeA mutant. The differentially expressed genes (DEGs) enriched in hyphal growth and conidiation were drastically transcribed from the comparatively transcriptomic profile between the wild type and ΔAaVeA mutant strains with or without light. In mycotoxin production, TeA biosynthesis seems no obvious effect by light regulation, but AOH and AME formation was significantly stimulated by blue light. Nevertheless, the disruption of AaVeA resulted in a marked decrease in mycotoxin production and the action of the stimulation was lost via blue light for the abundant accumulation of AOH and AME in the ΔAaVeA strain. From DEG expression and further verification by RT-qPCR, the loss of AaVeA caused the discontinuous supply of the substrates for mycotoxin biosynthesis and the drastic decline of biosynthetic gene expression. In addition, pathogenicity depends on AaVeA regulation in tomato infected by A. alternata in vivo. These findings provide a distinct understanding of the roles of AaVeA in fungal growth, development, mycotoxin biosynthesis and pathogenicity in response to various light sources.